1992
DOI: 10.1007/bf00130645
|View full text |Cite
|
Sign up to set email alerts
|

Effects of serial subculture in vitro on the endogenous levels of indole-3-acetic acid and abscisic acid and rootability in microcuttings of ?Jonathan? apple

Abstract: Proliferating axillary shoots of the difficult-to-root apple cultivar `Jonathan' acquired an enhanced ability to form adventitious roots with increasing number of subcultures in vitro . The transition between the difficult-to-root and the easy-to-root condition occurred at the fourth subculture .Endogenous levels of free IAA and ABA in shoot tissues were analysed by gas chromatography/mass spectrometry/single ion monitoring (GC/MS/SIM) using negative ion chemical ionisation . Tissues from the mother plants gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
3

Year Published

1994
1994
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 19 publications
1
16
0
3
Order By: Relevance
“…Another possibility is that environmental conditions prior to culture initiation, possibly resulting in altered growth regulator concentrations, gave rise to this contrast. Although correlations between ratios of indoleacetic acid and abscisic acid, and shoot production with time, have not been investigated with wild cherry, Noiton et al (1992) have demonstrated a correlation between this ratio and increasing rootability of apple shoots with subculturing.…”
Section: Discussionmentioning
confidence: 94%
“…Another possibility is that environmental conditions prior to culture initiation, possibly resulting in altered growth regulator concentrations, gave rise to this contrast. Although correlations between ratios of indoleacetic acid and abscisic acid, and shoot production with time, have not been investigated with wild cherry, Noiton et al (1992) have demonstrated a correlation between this ratio and increasing rootability of apple shoots with subculturing.…”
Section: Discussionmentioning
confidence: 94%
“…Several limitations such as low shoot proliferation in forest trees, excessive phenolic exudation (Linington 1991), basal callusing (Marks and Simpson 1994), vitrification (Monsalede et al 1995), and shoot tip necrosis (Bargchi and Alderson 1996) are pronounced in tree tissue culture. Further, difficulty in rooting (Noiton et al 1992;Harada and Murai 1996) has also had a negative effect on micropropagation of woody forest tree species in vitro. In this section we have attempted to describe the trend of research activities during the last decade.…”
Section: Micropropagation Of Tree Without Intervening Callus Phasementioning
confidence: 97%
“…Fuji, Starkrimson) and cultivar 'Jonathan' (Malus× domestica Borkh. ), proliferating axillary shoots acquired an enhanced rooting ability with increasing the number of subcultures in vitro (Chang et al 1991;Noiton et al 1992). Precocious walnut (Juglans regia L.) shoots have a high rooting rate by induction in vitro after they have been subcultured for 4 years (Pei et al 2002).…”
Section: Introductionmentioning
confidence: 98%